Affinity Tag for Protein Purification and Detection Based on the Disulfide-Linked Complex of InaD and NorpA - Michelle E. Kimple; John Sondek (BioTechniques)
Affinity tags are not only used for the expression and purification of recombinant proteins but also for the detection of protein-protein interactions. Common problems with many affinity tags are excessive length, which may interfere with the structure and function of tagged proteins, and low affinity and/or specificity for primary detection and purification agents. Preliminary results suggest that the C-terminal five residues of the Drosophila protein NorpA, based on the short, covalent interaction they make with the N-terminal PDZ domain (PDZ1) of InaD, are useful as a general affinity tag. First, a PDZ1-alkaline phosphatase fusion protein specifically detects both its physiological ligand and a heterologous protein expressing the NorpA C-terminal five residues. The interaction of PDZ1 with a NorpA-tagged protein is reversible by a reducing agent, which allows nitrocellulose membranes to be stripped completely and reused. In addition, a NorpA-tagged protein can specifically bind to immobilized PDZ1 resin, while other cellular proteins are washed through. After washing, the NorpA-tagged protein is eluted by a reducing buffer. The NorpA tag's short length makes it the smallest affinity tag available, and its specific and high-affinity interaction with PDZ1 could yield a powerful system that improves on currently available technology.